P36 Cancer prevention in vulnerable women: an exploratory qualitative study with women who have experienced domestic violence and offending behaviours. (September 2018) - Hanson, S; Gilbert, D; Landy, R; Okoli, G; Guell, C
Abstract : Background: Cancer is more common among disadvantaged communities. Women who have experienced domestic violence or offending behaviours are at higher risk of cancer through multiple risk factors: addictive behaviours, low levels of activity and poor screening uptake. Such women are also likely to come from socially marginalised backgrounds where persistent health inequity remains. Addressing their needs is an important factor in cancer prevention and early diagnosis. This exploratory study aimed to explore women's health behaviours in terms of excessive alcohol consumption, tobacco use, physical activity, diet, weight and cancer screening within their context and experiences of vulnerability. We also aimed to assess perceptions of risk to cancer and barriers to health promoting activities. Methods: We conducted 14 semi-structured interviews and two focus groups with vulnerable women attending support groups in a Housing Association women's centre, and seven interviews with the staff who support them. Verbatim transcripts were analysed thematically. Results: We identified three themes: risk factors as markers of distress, inhibiting views of self, and navigating the healthcare system. Risk factors of alcohol use, smoking, physical inactivity and unhealthy eating were common but reported in context of distressing experiences of mental ill-heath, poverty, addition and abuse. Walking, for example, was reported as the result of lost driving licences or a symptom of anxiety; smoking was reported as part of other additive behaviour such as alcohol abuse and drug taking. Women's views of themselves such as self-worth were often negative, shaped by experiences of neglect and abuse, or of perceived negative treatment by social and mental health services. This shaped their trust in health services, as well as low perception of risk for cancer susceptibility and potential for delay in presenting with cancer symptoms. Women frequently reported fatalistic attitudes to cancer, chronic diseases and early death but paradoxically also reported high levels of screening uptake. Despite narratives of distress, women showed self-reliance and resilience, and this might have helped navigating the health systems to some degree, for example using screening services. Women and staff were receptive to health promotion in cancer prevention. Conclusion: Women in this study were at high risk of chronic diseases, including cancer. Their experiences of social disadvantage and personal and structural violence profoundly shaped their practices, aspirations and attitudes towards risk, health and healthcare. Our findings will inform the design of a feasibility study to test a cancer prevention strategy co-designed by and tailored to vulnerable women.